2018
DOI: 10.1002/acn3.599
|View full text |Cite
|
Sign up to set email alerts
|

Mapt deletion fails to rescue premature lethality in two models of sodium channel epilepsy

Abstract: Deletion of Mapt, encoding the microtubule‐binding protein Tau, prevents disease in multiple genetic models of hyperexcitability. To investigate whether the effect of Tau depletion is generalizable across multiple sodium channel gene‐linked models of epilepsy, we examined the Scn1b −/− mouse model of Dravet syndrome, and the Scn8a N1768D/+ model of Early Infantile Epileptic Encephalopathy. Both models display severe seizures and early mortality. We found no prolongation of survival between Scn1b −/− ,Mapt +/+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, Tau protein KO also reduced Kcna1 –/– hippocampal network hyperexcitability in response to increased K + levels in vitro . However, MAPT (gene encoding for the microtubule-binding protein Tau) deletion failed to rescue premature lethality in sodium channel gene-linked epileptic encephalopathy in the mouse model of Dravet syndrome (DS) (Scn1b –/– ) and early infantile epileptic encephalopathy (Scn8a N1768D/+ ) …”
Section: Mechanistic Insights About Tau Protein In Epilepsy and Ad: F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Tau protein KO also reduced Kcna1 –/– hippocampal network hyperexcitability in response to increased K + levels in vitro . However, MAPT (gene encoding for the microtubule-binding protein Tau) deletion failed to rescue premature lethality in sodium channel gene-linked epileptic encephalopathy in the mouse model of Dravet syndrome (DS) (Scn1b –/– ) and early infantile epileptic encephalopathy (Scn8a N1768D/+ ) …”
Section: Mechanistic Insights About Tau Protein In Epilepsy and Ad: F...mentioning
confidence: 99%
“…25 However, MAPT (gene encoding for the microtubule-binding protein Tau) deletion failed to rescue premature lethality in sodium channel gene-linked epileptic encephalopathy in the mouse model of Dravet syndrome (DS) (Scn1b −/− ) and early infantile epileptic encephalopathy (Scn8a N1768D/+ ). 100 MAPT deletion did not affect the survival of Scn1b −/− −MAPT +/+ , Scn1b −/− − MAPT + / − , or Scn1b − / − − MAPT − / − mice or of Scn8a N1768D/+ −MAPT +/+ , Scn8a N1768D/+ −MAPT +/− , or Scn8a N1768D/+ −MAPT −/− mice implicating that MAPT deletion on genetic models of neural hyperexcitability did not affect the mouse models of epileptic ion channelopathy. 100 PTZ-kindled rats demonstrated increased levels of relative Tau protein phosphorylation and low level of total Tau protein.…”
Section: Mechanistic Insights About Tau Protein Inmentioning
confidence: 99%
See 1 more Smart Citation
“…33 We reported that intercrossing Scn1b +/− mice with Mapt +/− mice to generate Scn1b −/− /Mapt +/+ and Scn1b −/− /Mapt −/− progeny had no impact on seizures or survival of Scn1b −/− mice. 34 In other work, we reported that the time courses of maturation of neuronal GABAergic signaling in neocortical layer II/III and hippocampal CA1 or CA3 pyramidal cells are delayed in both the Scn1b −/− and Scn1a +/− mouse models of DEE, such that GABAergic signaling remains excitatory in these brain regions for significantly longer periods of development compared to WT. 28 This important point should be considered in the context of both DS and EIEE52 when discussing the effects of disinhibition, in that defects are not limited to impaired PV + neuron firing but also that inhibitory neurotransmission is further dampened by the impaired capacity of postsynaptic cells to receive these inputs as inhibitory.…”
Section: Discussionmentioning
confidence: 78%
“…Deletion of Mapt , the gene encoding the microtubule‐binding protein Tau, was shown to attenuate hyperexcitability and prevent disease in the Scn1a R1407X/+ mouse model of DS 33 . We reported that intercrossing Scn1b +/− mice with Mapt +/− mice to generate Scn1b −/− /Mapt +/+ and Scn1b −/− /Mapt −/− progeny had no impact on seizures or survival of Scn1b −/− mice 34 …”
Section: Discussionmentioning
confidence: 96%